3‐Dimensional Printing of Hydrogel‐Based Nanocomposites: A Comprehensive Review on the Technology Description, Properties, and Applications. Issue 10 (20th September 2021) - Soleymani Eil Bakhtiari, Sanaz; Bakhsheshi-Rad, Hamid Reza; Karbasi, Saeed; Razzaghi, Mahmood; Tavakoli, Mohamadreza; Ismail, Ahmad Fauzi; Sharif, Safian; RamaKrishna, Seeram; Chen, Xiongbiao; Berto, Filippo
Abstract : Increasing demand for customized implants and tissue scaffolds requires advanced biomaterials and fabricating processes for fabricating three‐dimensional (3D) structures that resemble the complexity of the extracellular matrix (ECM). Lately, biofabrication approaches such as cell‐laden (soft) hydrogel 3D printing (3DP) have been of increasing interest in the development of 3D functional environments similar to natural tissues and organs. Hydrogels that resemble biological ECMs can provide mechanical support and signaling cues to cells to control their behavior. Although the capability of hydrogels to produce artificial ECMs can regulate cellular behavior, one of the major drawbacks of working with hydrogels is their inferior mechanical properties. Therefore, keeping and enhancing the mechanical integrity of fabricated scaffolds has become an essential matter for 3D hydrogel structures. Herein, 3D‐printed hydrogel‐based nanocomposites (NCs) are evaluated systematically in terms of introducing novel techniques for 3DP of hydrogel‐based materials, properties, and biomedical applications. Abstract : This review article introduces novel techniques for the manufacturing of 3D‐printed hydrogel‐based nanocomposites. The aim of the article is to evaluate mechanical and biological properties of nanocomposites hydrogels to ensure their capability for handling and use for biomedical applications. The biomedical applications of nanocomposite hydrogels are presented.